The concept of parent involvement. Some theoretical and empirical considerations - Bakker, Joep; Denessen, Eddie (International Journal about Parents in Education, 2023)
This paper focuses on some conceptual and methodological problems inherent in many empirical studies on parental involvement.  On the basis of twelve selected studies in which quantitative measures for parent involvement have been used, we discuss the reasons for the diversity of empirical outcomes, partly due to the complexity and multi-dimensionality of the concept, but also due to the variety of operationalizations as well as methods that have been applied to assess parents’ levels of involvement.  In particular, empirical evidence of involvement obtained with questionnaires should be considered as doubtful because of the biases in ratings, whereas the use of multiple informants, as suggested in the literature, does not seem satisfactory to overcome this problem.  We suggest the use more qualitative methods for measuring parent involvement, for example by interviewing parents in depth about their own accounts for their behaviours.  This seems also the best guarantee to detect the more hidden features of their involvement in their children’s education.